ANALISIS PENGARUH FAKTOR KINERJA PEGAWAI DINAS PARIWISATA DAN KEBUDAYAAN KABUPATEN SOLOK SELATAN - Heryanto, Heryanto (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2024)
Employee Performance shows the work performance achieved by employees in accordance with their responsibilities. The aim of the research is how organizational culture, leadership and rewards together influence the performance of employees at the Tourism and Culture Office of South Solok Regency. This study uses quantitative methods. In this research, the population is all Civil Servants at the South Solok Regency Tourism and Culture Office, totaling 35 people. The sample is all members of the population used as a sample, namely 35 civil servants at the South Solok Regency Tourism and Culture Office. The data analysis technique used in this research is multiple regression analysis. The results of this research show that Organizational Culture, Leadership, and Rewards together have a significant positive effect on Employee Performance. Next, to see whether this model is good or not can be seen from the goodness of fit test. The determinant coefficient (R2) is good, shown by the contribution of the independent variables consisting of Organizational Culture, Leadership, Rewards to the Performance variable of 66.9% and the contribution of other factors is 33.1%.